The effect of implementing green accounting on the environmental performance of cement, energy, and mining companies in Indonesia - Fransisca Melenia; Aisa Tri Agustini; Hendrawan Santosa Putra (Universitas Hayam Wuruk Perbanas, 2023)
This study aims to examine the effect of implementing green accounting on the environmental performance of cement, energy, and mining companies in Indonesia. This study is a quantitative study. The data used are secondary data obtained from sustainability reports of cement, energy, and mining companies listed on the Indonesia Stock Exchange (IDX) during the period of 2017-2020. The data analysis method used in this study is partial least squares using the WarpPLS 7.0 program. The results show that the implementation of green accounting in the form of renewable energy has a negative effect on environmental performance. The implementation of green accounting in the form of recycled waste has a significant positive effect on environmental performance. Meanwhile, the implementation of green accounting in the form of environmental costs has no effect on environmental performance.